Waste-to-value: Optimizing methanotrophic culture enrichment from activated sludge using a synthetic wastewater effluent - Lisa Stephanie H. Dizon; Robert S. Bertrand; William E. Holmes; Rafael A. Hernandez; Andrei Y. Chistoserdov; Wayne W. Sharp; Dhan Lord B. Fortela; Mark E. Zappi; Emmanuel D. Revellame (Journal of Environmental Chemical Engineering, 2026)

Impact of climate change on freshwater macronutrients and agricultural yields across Britain - Nathan Missault; Victoria A. Bell; David M. Cooper; Ryan T. Sharp; Andrew P. Whitmore; Alice E. Milne; Helen N. Davies (Journal of Environmental Management, 2026)

Rethinking land-use Strategies: A multi-objective analysis of combined sparing and sharing approaches applied across great britain - Imane El Fartassi; Ryan T. Sharp; Victoria A. Bell; Andrew P. Whitmore; Helen Metcalfe; Nathan Missault; John Redhead; David M. Cooper; Jonathan Storkey; Helen Davies; Theo Jackson; Kevin Coleman; et al. (Journal of Environmental Management, 2026)

A Sponge Mortality Event Associated With a Picocyanobacterial Bloom in a Semi-Enclosed Basin in Central Florida Bay, USA - William C. Sharp; Gabriel A. Delgado; Jennifer Cannizzaro; Chuanmin Hu; Sharla Sugierski; Rachel J. Harris (Estuaries and Coasts, 2026)
Sponges historically dominated the heterotrophic biomass of Florida Bay’s hard-bottom communities, and the ecological services they provide have long been recognized. However, these communities have become degraded over the last several decades, in part, due to periodic cyanobacterial blooms. During August 2013 a detailed assessment of a sponge community across a semi-enclosed basin within central Florida Bay, colloquially known as Mystery Basin, that supported a heathy sponge community was concluded. During September 2013, reduced water visibility and water discoloration — consistent with past picocyanobacterial blooms in Florida Bay — were observed. Satellite imagery confirmed that a cyanobacteria bloom started in early September and ended in December 2013. The sponge community was re-surveyed in early 2014 at a subset of the original survey sites. Of the 21 sponge taxa identified at those sites during 2013, 12 were not observed during the 2014 survey, including three species ( Spheciospongia vesparium , Ircinia felix , Geodia gibberosa ) that collectively accounted for approximately 95% of the pre-bloom sponge biomass. Subsequent surveys conducted during 2015 and 2016 revealed a sponge community dominated by fast-growing weedy species. Of the three formally dominant species, S. vesparium remained absent, and only a few individuals of I. felix and a single individual of G. gibberosa were observed. These results underscore the effects of the cyanobacterial blooms on Florida Bay’s sponge communities, the protracted recolonization period necessary once those communities are affected, and the challenges that assisted sponge restoration efforts will encounter in the face of continued cyanobacterial blooms.

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

The mycobiome of Cassiopea xamachana as determined by culture-based and metagenomic sequencing - Victoria Sharp; Marta Mammone; Charles Dye; Raúl A. González-Pech; Oded Yarden; Mónica Medina (Symbiosis, 2025)

Assimilatory processes dominate diel inorganic nitrogen cycling in a shallow open-water constructed wetland - Richard L. Smith; Ariel P. Reed; Deborah A. Repert; Craig R. Tobias; Jonathan O. Sharp (Science of The Total Environment, 2025)

Effectiveness of steam cleaning technology on reducing the occurrence of ESKAPE organisms and Escherichia coli in the stables of an equine referral hospital - S. Sosa-Portugal; L. Dale; J. Devaney; A. Sharp; F. Malalana; D. Timofte (Journal of Equine Veterinary Science, 2025)

Hypertonic Saline Nasal Rinse Intervention: Immunomodulatory Effects in Dairy Workers - Grant Erlandson; Sheryl Magzamen; Julia L. Sharp; James Seidel; Jill A. Poole; Mary Bradford; Joshua W. Schaeffer (Journal of Agromedicine, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Micronization of wholewheat flour increases iron bioavailability from hydrothermally processed wheat flour dough - Mohamad F. Aslam; Sarah M. Arafsha; Sarah E. Berry; Balazs Bajka; Peter R. Ellis; Gladys O. Latunde-Dada; Paul A. Sharp (Food Research International, 2024)

Elemental characterization of electronic waste: a review of research methodologies and applicability to the practice of e-waste recycling - Amarachukwu Agbim; Kelsea A. Schumacher; Nicholas Sharp; Rick Paul; Ruthmara Corzo (Waste Management, 2024)

Perception of Body Fat and Body Fat Percentages Among Female College Students - M. Schmidt; D. Beeson; S. Keck; T. Pulver; M. Scott; N. Sharp; E. Weaver; C. Lyman; A. Grady (Journal of the Academy of Nutrition and Dietetics, 2024)

Anticoagulant rodenticide exposure in common buzzards: Impact of new rules for rodenticide use - Sheila George; E. Sharp; S. Campbell; A. Giela; C. Senior; L.M. Melton; D. Vyas; L. Mocogni; M. Galloway (Science of The Total Environment, 2024)

Moche chronology of ancient Peru: Bayesian assessment of radiocarbon dates and ceramic styles from north to south - Michele L. Koons; Branden Cesare Rizzuto; Lisa Trever; Alicia Boswell; Augusto Bazán Pérez; Luis A. Muro Ynoñán; Gabriel Prieto; Carlos Rengifo; Kayeleigh Sharp; Edward Swenson; Hugo Ikehara-Tsukayama; Jessica Ortiz Zevallos; et al. (Quaternary International, 2024)

The impact of behavioural weight management interventions on eating behaviour traits in adults with overweight or obesity: a systematic review and meta-analysis - Laura Kudlek; Patricia Eustacio Colombo; Amy Ahern; Struan Tait; Natasha Reid; Milindu Wickramarachchi; Aiswarya Lakshmi; Stephen J. Sharp; Marie Spreckley; Julia Mueller; Rebecca A. Jones (Appetite, 2024)

Leveraging satellite observations to reveal ecological drivers of pest densities across landscapes - Sara E. Emery; Jay A. Rosenheim; Rebecca Chaplin-Kramer; Richard Sharp; Daniel S. Karp (Science of The Total Environment, 2024)

The mobility of the brachycephalic canine nostril in relation to the degree of nostril stenosis - C.A.T. Sharp; N.-C. Liu; A. Guy; J.F. Ladlow (The Veterinary Journal, 2024)

Bear biometrics: developing an individual recognition technique for sloth bears - Ashish Kumar Jangid; Arun A. Sha; Swayam Thakkar; Nishchay Chawla; Baijuraj M. V.; Thomas Sharp; Kartick Satyanarayan; Geeta Seshamani (Mammalian Biology, 2024)

Public perceptions of per- and polyfluoroalkyl substances (PFAS): Psycho-demographic characteristics differentiating PFAS knowledge and concern - Joya A. Kemper; Emma Sharp; Shan Yi; Erin M. Leitao; Lokesh P. Padhye; Melanie Kah; Jack L.-Y. Chen; Kapish Gobindlal (Journal of Cleaner Production, 2024)

The effects of gonadal hormones on heroin Self-Administration in male gonadectomized rats - Mark A. Smith; Tallia Pearson; Shannon L. Ballard; Jacob D. Camp; Jessica L. Sharp (Psychopharmacology, 2024)

Uncertainty sources for measurable ocean carbonate chemistry variables - Brendan R. Carter; Jonathan D. Sharp; Andrew G. Dickson; Marta Álvarez; Michael B. Fong; Maribel I. García‐Ibáñez; Ryan J. Woosley; Yuichiro Takeshita; Leticia Barbero; Robert H. Byrne; Wei‐Jun Cai; Melissa Chierici; et al. (Limnology and Oceanography, 2024)
The ocean carbonate system is critical to monitor because it plays a major role in regulating Earth's climate and marine ecosystems. It is monitored using a variety of measurements, and it is commonly understood that all components of seawater carbonate chemistry can be calculated when at least two carbonate system variables are measured. However, several recent studies have highlighted systematic discrepancies between calculated and directly measured carbonate chemistry variables and these discrepancies have large implications for efforts to measure and quantify the changing ocean carbon cycle. Given this, the Ocean Carbonate System Intercomparison Forum (OCSIF) was formed as a working group through the Ocean Carbon and Biogeochemistry program to coordinate and recommend research to quantify and/or reduce uncertainties and disagreements in measurable seawater carbonate system measurements and calculations, identify unknown or overlooked sources of these uncertainties, and provide recommendations for making progress on community efforts despite these uncertainties. With this paper we aim to (1) summarize recent progress toward quantifying and reducing carbonate system uncertainties; (2) advocate for research to further reduce and better quantify carbonate system measurement uncertainties; (3) present a small amount of new data, metadata, and analysis related to uncertainties in carbonate system measurements; and (4) restate and explain the rationales behind several OCSIF recommendations. We focus on open ocean carbonate chemistry, and caution that the considerations we discuss become further complicated in coastal, estuarine, and sedimentary environments.

Municipal separate storm sewer system (MS4) dry weather flows and potential flow sources as assessed by conventional and advanced bacterial analyses - Dong Li; Laurie C. Van De Werfhorst; Jared Ervin; Aaron Poresky; Brandon Steets; Cindy Rivers; Grant Sharp; Jen Smith; Patricia A. Holden (Environmental Pollution, 2023)

Feasibility and acceptability of an acceptance-based guided self-help programme for weight loss maintenance - Julia Mueller; Rebecca A. Jones; Rebecca Richards; Jennifer Woolston; Fiona Whittle; Andrew J. Hill; Carly A. Hughes; Robbie Duschinsky; Stephen J. Sharp; Clare Boothby; Jennifer Bostock; Penny Breeze; et al. (Appetite, 2023)

Non-industrial private forest owners' preferences for fuel reduction cost-share programs in the southeastern U.S. - Jana Hilsenroth; Kelly A. Grogan; Raelene M. Crandall; Ludie Bond; Misti Sharp (Forest Policy and Economics, 2023)

Sustained ICP Elevation Is a Driver of Spatial Memory Deficits After Intraventricular Hemorrhage and Leads to Activation of Distinct Microglial Signaling Pathways - Chloe H. Puglisi; Bradley P. Ander; Catherine Peterson; Janet A. Keiter; Heather Hull; Cameron W. Hawk; Venina S. Kalistratova; Ali Izadi; Gene G. Gurkoff; Frank R. Sharp; Ben Waldau (Translational Stroke Research, 2023)

The role of trade in pacific food security and nutrition - T.D. Brewer; N.L. Andrew; D. Abbott; R. Detenamo; E.N. Faaola; P.V. Gounder; N. Lal; K. Lui; A. Ravuvu; D. Sapalojang; M.K. Sharp; R.J. Sulu; et al. (Global Food Security, 2023)

Structural characterization and biological activity of an α-glucan from the mollusk Marcia hiantina (Lamarck, 1818) - Hoda Al. Ahmed; Bernadeth F. Ticar; Ian Black; Fakhri Mahdi; Anter A. Shami; Sandeep K. Misra; Christian Heiss; Jason J. Paris; Joshua S. Sharp; Parastoo Azadi; Vitor H. Pomin (Glycoconjugate Journal, 2023)

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Use of multiple endpoints to assess the impact of captivity on gut flora diversity in Long Island Sound Fundulus heteroclitus - Joseph P. Battaglia; Christian M. Kearney; Kirsten Guerette; Jordan Corbishley; Emily Sanchez; Brennah Kent; Hanna Storie; Emma Sharp; Shane Martin; Matthew Saberito; Jonathan D. Blake; Richard S. Feinn; et al. (Environmental Biology of Fishes, 2022)

The first three records of killer whales ( Orcinus orca ) killing and eating blue whales ( Balaenoptera musculus ) - John A. Totterdell; Rebecca Wellard; Isabella M. Reeves; Brodie Elsdon; Pia Markovic; Machi Yoshida; Ashleigh Fairchild; Gemma Sharp; Robert L. Pitman (Marine Mammal Science, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Safety and Pharmacokinetics of Intranasally Administered Heparin - Hannah M. Harris; Katherine L. Boyet; Hao Liu; Rohini Dwivedi; Nicole M. Ashpole; Ritesh Tandon; Gene L. Bidwell; Zhi Cheng; Lauren A. Fassero; Christian S. Yu; Vitor H. Pomin; Dipanwita Mitra; et al. (Pharmaceutical Research, 2022)

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

Correction to: Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)

Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)
Purpose Heat stress exacerbates post-exercise hypotension (PEH) and cardiovascular disturbances from elevated body temperature may contribute to exertion-related incapacity. Mast cell degranulation and muscle mass are possible modifiers, though these hypotheses lack practical evidence. This study had three aims: (1) to characterise pre–post-responses in histamine and mast cell tryptase (MCT), (2) to investigate relationships between whole body muscle mass (WBMM) and changes in blood pressure post-marathon, (3) to identify any differences in incapacitated runners. Methods 24 recreational runners were recruited and successfully completed the 2019 Brighton Marathon (COMPLETION). WBMM was measured at baseline. A further eight participants were recruited from incapacitated runners (COLLAPSE). Histamine, MCT, blood pressure, heart rate, body temperature and echocardiographic measures were taken before and after exercise (COMPLETION) and upon incapacitation (COLLAPSE). Results In completion, MCT increased by nearly 50% from baseline ( p = 0.0049), whereas histamine and body temperature did not vary ( p > 0.946). Systolic (SBP), diastolic (DBP) and mean (MAP) arterial blood pressures and systemic vascular resistance (SVR) declined ( p < 0.019). WBMM negatively correlated with $$Δ $$ Δ SBP ( r = − 0.43, p = 0.046). For collapse versus completion, there were significant elevations in MCT (1.77 ± 0.25 μg/L vs 1.18 ± 0.43 μg/L, p = 0.001) and body temperature (39.8 ± 1.3 °C vs 36.2 ± 0.8 °C, p < 0.0001) with a non-significant rise in histamine (9.6 ± 17.9 μg/L vs 13.7 ± 33.9 μg/L, p = 0.107) and significantly lower MAP, DBP and SVR ( p < 0.033). Conclusion These data support the hypothesis that mast cell degranulation is a vasodilatory mechanism underlying PEH and exercise associated collapse. The magnitude of PEH is inversely proportional to the muscle mass and enhanced by concomitant body heating.

Insulin regulates human mammosphere development and function - Ashalyn P. Watt; Christophe Lefevre; Cynthia S. Wong; Kevin R. Nicholas; Julie A. Sharp (Cell and Tissue Research, 2021)

Modulation of heroin intake by ovarian hormones in gonadectomized and intact female rats - Mark A. Smith; Sarah B. Ethridge; Tallia Pearson; Huailin Zhang; Madison M. Marcus; Shannon L. Ballard; Alexander T. Casimir; Kenzie M. Potter; Karl T. Schmidt; Jessica L. Sharp; Andrea M. Robinson (Psychopharmacology, 2021)

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

Self-reported health and survival in older patients diagnosed with multiple myeloma - Nadia A. Nabulsi; Ali Alobaidi; Brian Talon; Alemseged A. Asfaw; Jifang Zhou; Lisa K. Sharp; Karen Sweiss; Pritesh R. Patel; Naomi Y. Ko; Brian C.-H. Chiu; Gregory S. Calip (Cancer Causes & Control, 2020)

Exploring adoption price effects on life cycle inventory results - Shelie A. Miller; Benjamin E. Sharp; Jim F. Chamberlain; Saumya Sarkar; Shamitha Keerthi (The International Journal of Life Cycle Assessment, 2020)

Enhanced tactile identification of musical emotion in the deaf - Andréanne Sharp; B. A. Bacon; F. Champoux (Experimental Brain Research, 2020)

Capitalizing on an ecological process to aid coral reef ecosystem restoration: Can gastropod trophodynamics enhance coral survival? - Gabriel A. Delgado; William C. Sharp (Coral Reefs, 2020)

Reference points for predators will progress ecosystem‐based management of fisheries - Simeon L. Hill; Jefferson Hinke; Sophie Bertrand; Lowell Fritz; Robert W. Furness; James N. Ianelli; Matthew Murphy; Ricardo Oliveros‐Ramos; Lorien Pichegru; Rowland Sharp; Richard A. Stillman; Peter J. Wright; et al. (Fish and Fisheries, 2020)
Ecosystem‐based management of fisheries aims to allow sustainable use of fished stocks while keeping impacts upon ecosystems within safe ecological limits. Both the FAO Code of Conduct for Responsible Fisheries and the Aichi Biodiversity Targets promote these aims. We evaluate implementation of ecosystem‐based management in six case‐study fisheries in which potential indirect impacts upon bird or mammal predators of fished stocks are well publicized and well studied. In particular, we consider the components needed to enable management strategies to respond to information from predator monitoring. Although such information is available in all case‐studies, only one has a reference point defining safe ecological limits for predators and none has a method to adjust fishing activities in response to estimates of the state of the predator population. Reference points for predators have been developed outside the fisheries management context, but adoption by fisheries managers is hindered a lack of clarity about management objectives and uncertainty about how fishing affects predator dynamics. This also hinders the development of adjustment methods because these generally require information on the state of ecosystem variables relative to reference points. Nonetheless, most of the case‐studies include precautionary measures to limit impacts on predators. These measures are not used tactically and therefore risk excessive restrictions on sustainable use. Adoption of predator reference points to inform tactical adjustment of precautionary measures would be an appropriate next step towards ecosystem‐based management.

Functional evaluation of a monotreme-specific antimicrobial protein, EchAMP, against experimentally induced mastitis in transgenic mice - Manjusha Neerukonda; Sivapriya Pavuluri; Isha Sharma; Alok Kumar; Purnima Sailasree; Jyothi B Lakshmi; Julie A. Sharp; Satish Kumar (Transgenic Research, 2019)

Vortioxetine reverses medial prefrontal cortex-mediated cognitive deficits in male rats induced by castration as a model of androgen deprivation therapy for prostate cancer - Alexandra M. Sharp; Suphada Lertphinyowong; Samantha S. Yee; Denisse Paredes; Jonathan Gelfond; Teresa L. Johnson-Pais; Robin J. Leach; Michael Liss; April L. Risinger; Anna C. Sullivan; Ian M. Thompson; David A. Morilak (Psychopharmacology, 2019)

Dissolution Testing in Drug Product Development: Workshop Summary Report - Andreas Abend; David Curran; Jesse Kuiper; Xujin Lu; Hanlin Li; Andre Hermans; Pramod Kotwal; Dorys A. Diaz; Michael J. Cohen; Limin Zhang; Erika Stippler; German Drazer; et al. (The AAPS Journal, 2019)

Peptide Inhibitor of Complement C1 (PIC1) Inhibits Growth of Pathogenic Bacteria - Pamela S. Hair; Magdielis Gregory Rivera; Adrianne I. Enos; Susan E. Pearsall; Julia A. Sharp; Nazita Yousefieh; Frank A. Lattanzio; Neel K. Krishna; Kenji M. Cunnion (International Journal of Peptide Research and Therapeutics, 2019)

The structure and context of male and female song in White-throated Dippers - Lucy Magoolagan; Peter J. Mawby; Flora A. Whitehead; Stuart P. Sharp (Journal of Ornithology, 2019)

Ozone pollution will compromise efforts to increase global wheat production - Gina Mills; Katrina Sharps; David Simpson; Håkan Pleijel; Malin Broberg; Johan Uddling; Fernando Jaramillo; William J Davies; Frank Dentener; Maurits Van den Berg; Madhoolika Agrawal; Shahibhushan B. Agrawal; et al. (Global Change Biology, 2018)
Introduction of high‐performing crop cultivars and crop/soil water management practices that increase the stomatal uptake of carbon dioxide and photosynthesis will be instrumental in realizing the United Nations Sustainable Development Goal ( SDG ) of achieving food security. To date, however, global assessments of how to increase crop yield have failed to consider the negative effects of tropospheric ozone, a gaseous pollutant that enters the leaf stomatal pores of plants along with carbon dioxide, and is increasing in concentration globally, particularly in rapidly developing countries. Earlier studies have simply estimated that the largest effects are in the areas with the highest ozone concentrations. Using a modelling method that accounts for the effects of soil moisture deficit and meteorological factors on the stomatal uptake of ozone, we show for the first time that ozone impacts on wheat yield are particularly large in humid rain‐fed and irrigated areas of major wheat‐producing countries (e.g. United States, France, India, China and Russia). Averaged over 2010–2012, we estimate that ozone reduces wheat yields by a mean 9.9% in the northern hemisphere and 6.2% in the southern hemisphere, corresponding to some 85 Tg (million tonnes) of lost grain. Total production losses in developing countries receiving Official Development Assistance are 50% higher than those in developed countries, potentially reducing the possibility of achieving UN SDG 2. Crucially, our analysis shows that ozone could reduce the potential yield benefits of increasing irrigation usage in response to climate change because added irrigation increases the uptake and subsequent negative effects of the pollutant. We show that mitigation of air pollution in a changing climate could play a vital role in achieving the above‐mentioned UN SDG , while also contributing to other SDG s related to human health and well‐being, ecosystems and climate change.

Phosphodiesterase 4 inhibition affects both the direct and indirect pathway: an electrophysiological study examining the tri-phasic response in the substantia nigra pars reticulata - P. R. A. Heckman; J. V. Schweimer; T. Sharp; J. Prickaerts; A. Blokland (Brain Structure and Function, 2018)

Pharmacological evidence that 5-HT2C receptor blockade selectively improves decision making when rewards are paired with audiovisual cues in a rat gambling task - Wendy K. Adams; Chris Barkus; Jacqueline-Marie N. Ferland; Trevor Sharp; Catharine A. Winstanley (Psychopharmacology, 2017)

Functional neuroimaging of visuo-vestibular interaction - R. E. Roberts; H. Ahmad; Q. Arshad; M. Patel; D. Dima; R. Leech; B. M. Seemungal; D. J. Sharp; A. M. Bronstein (Brain Structure and Function, 2017)

Molecular variability and phylogenetic relationships of guava (Psidium guajava L.) cultivars using inter-primer binding site (iPBS) and microsatellite (SSR) markers - A. Mehmood; S. Luo; N. M. Ahmad; C. Dong; T. Mahmood; Y. Sajjad; M. J. Jaskani; P. Sharp (Genetic Resources and Crop Evolution, 2016)

Analysis of human breast milk cells: gene expression profiles during pregnancy, lactation, involution, and mastitic infection - Julie A. Sharp; Christophe Lefèvre; Ashalyn Watt; Kevin R. Nicholas (Functional & Integrative Genomics, 2016)

Retrospective stable isotope analysis reveals ecosystem responses to river regulation over the last century - Thomas F. Turner; Trevor J. Krabbenhoft; Michael L. Collyer; Corey A. Krabbenhoft; Melanie S. Edwards; Zachary D. Sharp (Ecology, 2015)
Disruption of natural flow regimes, nutrient pollution, and other consequences of human population growth and development have impacted most major rivers of the world. Alarming losses of aquatic biodiversity coincide with human‐caused river alteration, but effects of biotic homogenization on aquatic ecosystem processes are not as well documented. This is because unaltered systems for comparison are scarce, and some ecosystem‐wide effects may take decades to manifest. We evaluated aquatic ecosystem responses to extensive river‐floodplain engineering and nutrient addition in the Rio Grande of southwestern North America as revealed by changes in trophic structure of, and resource availability to, the fish community. Stable Isotope Analysis (SIA) was conducted on museum‐preserved fishes collected over a 70‐year period of intensive river management and exponential human population growth. Trophic complexity and resource heterogeneity for fish consumers (measured as “isotopic niche breadth”) decreased following sediment deprivation and channelization, and these effects persist into the present. Increased nutrient inputs led to δ 15 N enrichment in the entire fish community at all affected sites, and a shift to autochthonous sources of carbon at the most proximal site downstream of wastewater release, probably via bottom‐up transfer. Overall, retrospective SIA of apex consumers suggests radical change and functional impairment of a floodplain river ecosystem already marked by significant biodiversity loss.

The geology of the carbonate-hosted Blende Ag–Pb–Zn deposit, Wernecke Mountains, Yukon, Canada - Micheal Moroskat; Sarah A. Gleeson; R. J. Sharp; A. Simonetti; C. J. Gallagher (Mineralium Deposita, 2015)

Physiological Employment Standards III: physiological challenges and consequences encountered during international military deployments - Bradley C. Nindl; John W. Castellani; Bradley J. Warr; Marilyn A. Sharp; Paul C. Henning; Barry A. Spiering; Dennis E. Scofield (European Journal of Applied Physiology, 2013)

Assessing the sensitivity of habitats to fishing: from seabed maps to sensitivity maps a - N. C. Eno; C. L. J. Frid; K. Hall; K. Ramsay; R. A. M. Sharp; D. P. Brazier; S. Hearn; K. M. Dernie; K. A. Robinson; O. A. L. Paramor; L. A. Robinson (Journal of Fish Biology, 2013)
In the Welsh part of the Irish Sea, a method was developed for assessing the sensitivity of different seabed habitats to existing fishing activities, across a range of potential fishing intensities. The resistance of 31 habitats and their associated biological assemblage to damage by 14 categories of fishing activity were assessed along with the rate at which each habitat would recover following impact (resilience). Sensitivity was scored based on a combination of the resistance of a habitat to damage and its subsequent rate of recovery. The assessments were based, wherever possible, on scientific literature, with expert judgement used to extrapolate results to habitat and gear combinations not directly examined in the published literature. The resulting sensitivity matrices were then subject to further peer review at a series of workshops. Following consensus on the habitat sensitivity, these data were combined with the most resolved sea‐floor habitat maps. These habitat sensitivity maps can help inform the development of site‐specific management plans, as well as having a place in spatial planning and aiding managers in developing dialogue with other stakeholders. A case study of their application is provided.

Habitat Restoration and Flood Control Protection in the Kissimmee River - Tate O. McAlpin; Jeremy A. Sharp; Stephen H. Scott; Gaurav Savant (Wetlands, 2013)

A Stochastic Approach to Model Dynamic Systems in Life Cycle Assessment - Shelie A. Miller; Stephen Moysey; Benjamin Sharp; Jose Alfaro (Journal of Industrial Ecology, 2013)
Summary This article presents a framework to evaluate emerging systems in life cycle assessment (LCA). Current LCA methods are effective for established systems; however, lack of data often inhibits robust analysis of future products or processes that may benefit the most from life cycle information. In many cases the life cycle inventory (LCI) of a system can change depending on its development pathway. Modeling emerging systems allows insights into probable trends and a greater understanding of the effect of future scenarios on LCA results. The proposed framework uses Bayesian probabilities to model technology adoption. The method presents a unique approach to modeling system evolution and can be used independently or within the context of an agent‐based model (ABM). LCA can be made more robust and dynamic by using this framework to couple scenario modeling with life cycle data, analyzing the effect of decision‐making patterns over time. Potential uses include examining the changing urban metabolism of growing cities, understanding the development of renewable energy technologies, identifying transformations in material flows over space and time, and forecasting industrial networks for developing products. A switchgrass‐to‐energy case demonstrates the approach.

A simple temperature-based model predicts the upper latitudinal limit of the temperate coral Astrangia poculata - J. L. Dimond; A. H. Kerwin; R. Rotjan; K. Sharp; F. J. Stewart; D. J. Thornhill (Coral Reefs, 2013)

Apical-Ventricular Cannula for Aortic Valve Bypass Therapy - Kevin G. Soucy; Joel D. Graham; Carrie J. Benzinger; M. Keith Sharp; Guruprasad A. Giridharan; Michael A. Sobieski; Mark S. Slaughter; Steven C. Koenig (Cardiovascular Engineering and Technology, 2013)

Aquifer-yield continuum as a guide and typology for science-based groundwater management - Suzanne A. Pierce; John M. Sharp; Joseph H. A. Guillaume; Robert E. Mace; David J. Eaton (Hydrogeology Journal, 2013)

Variability and change in the Canadian cryosphere - C. Derksen; S. L. Smith; M. Sharp; L. Brown; S. Howell; L. Copland; D. R. Mueller; Y. Gauthier; C. G. Fletcher; A. Tivy; M. Bernier; J. Bourgeois; et al. (Climatic Change, 2012)
During the International Polar Year (IPY), comprehensive observational research programs were undertaken to increase our understanding of the Canadian polar cryosphere response to a changing climate. Cryospheric components considered were snow, permafrost, sea ice, freshwater ice, glaciers and ice shelves. Enhancement of conventional observing systems and retrieval algorithms for satellite measurements facilitated development of a snapshot of current cryospheric conditions, providing a baseline against which future change can be assessed. Key findings include: 1. surface air temperatures across the Canadian Arctic exhibit a warming trend in all seasons over the past 40 years. A consistent pan-cryospheric response to these warming temperatures is evident through the analysis of multi-decadal datasets; 2. in recent years (including the IPY period) a higher rate of change was observed compared to previous decades including warming permafrost, reduction in snow cover extent and duration, reduction in summer sea ice extent, increased mass loss from glaciers, and thinning and break-up of the remaining Canadian ice shelves. These changes illustrate both a reduction in the spatial extent and mass of the cryosphere and an increase in the temporal persistence of melt related parameters. The observed changes in the cryosphere have important implications for human activity including the close ties of northerners to the land, access to northern regions for natural resource development, and the integrity of northern infrastructure.

Monotremes and marsupials: Comparative models to better understand the function of milk - Sanjana Kuruppath; Swathi Bisana; Julie A Sharp; Christophe Lefevre; Satish Kumar; Kevin R Nicholas (Journal of Biosciences, 2012)

Evaluation of PRDM9 variation as a risk factor for recurrent genomic disorders and chromosomal non-disjunction - Christelle Borel; Fanny Cheung; Helen Stewart; David A. Koolen; Christopher Phillips; N. Simon Thomas; Patricia A. Jacobs; Stephan Eliez; Andrew J. Sharp (Human Genetics, 2012)

An Integrated WebGIS Framework for Volunteered Geographic Information and Social Media in Soil and Water Conservation - Joshua D. Werts; Elena A. Mikhailova; Christopher J. Post; Julia L. Sharp (Environmental Management, 2012)

The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (Ambio, 2011)

Spatial movement optimization in Amazonian Eciton burchellii army ants - S. K. Willson; R. Sharp; I. P. Ramler; A. Sen (Insectes Sociaux, 2011)

Impact of PSA testing and prostatic biopsy on cancer incidence and mortality: comparative study between the Republic of Ireland and Northern Ireland - A-E. Carsin; F. J. Drummond; A. Black; P. J. van Leeuwen; L. Sharp; L. J. Murray; D. Connolly; L. Egevad; M. Boniol; P. Autier; H. Comber; A. Gavin (Cancer Causes & Control, 2010)

Combined resistance and endurance training improves physical capacity and performance on tactical occupational tasks - Nathan R. Hendrickson; Marilyn A. Sharp; Joseph A. Alemany; Leila A. Walker; Everett A. Harman; Barry A. Spiering; Disa L. Hatfield; Linda M. Yamamoto; Carl M. Maresh; William J. Kraemer; Bradley C. Nindl (European Journal of Applied Physiology, 2010)

Activation of 5-HT6 receptors facilitates attentional set shifting - Katherine E. Burnham; Mark G. Baxter; John R. Bainton; Eric Southam; Lee A. Dawson; David M. Bannerman; Trevor Sharp (Psychopharmacology, 2010)

A novel approach identified the FOLR1 gene, a putative regulator of milk protein synthesis - Karensa K. Menzies; Christophe Lefèvre; Julie A. Sharp; Keith L. Macmillan; Paul A. Sheehy; Kevin R. Nicholas (Mammalian Genome, 2009)

Effect of Low-Frequency Pulsatile Flow on Expression of Osteoblastic Genes by Bone Marrow Stromal Cells - Lindsay A. Sharp; Yong W. Lee; Aaron S. Goldstein (Annals of Biomedical Engineering, 2009)

Is seagrass an important nursery habitat for the Caribbean spiny lobster, panulirus argus , in Florida? - Donald C. Behringer; Mark J. Butler; William F. Herrnkind; John H. Hunt; Charles A. Acosta; William C. Sharp (New Zealand Journal of Marine and Freshwater Research, 2009)
Caribbean spiny lobster (Panulirus argus) settle preferentially in macroalgal‐covered hard‐bottom habitat, but seagrass is more prevalent in Florida (United States) and the Caribbean, so even low settlement of lobsters within seagrass could contribute substantially to recruitment if post‐settlement survival and growth were high. We tested the role of seagrass and hard‐bottom habitats for P. argus recruitment in three ways. We first explored possible density‐dependent regulation of early benthic juvenile lobster survival within cages deployed in seagrass and hard‐bottom habitats. Second, we compared settlement and survival of P. argus in both habitats, by comparing the recovery of microwire‐tagged early benthic juveniles from patches of seagrass and hard‐bottom. Finally, we assessed the relative abundance of juvenile lobsters in each habitat by deploying artificial structures in seagrass sites and compared these data with data from similar deployments of artificial structures in hard‐bottom habitat in other years. More early benthic juvenile lobsters were recovered from cages placed in hard‐bottom than in seagrass, but mortality of the early benthic life stage was high in both habitats. In regional surveys, the mean number of lobsters recovered from artificial shelters deployed within seagrass was lower than in any year that we sampled hard‐bottom, indicating that fewer lobsters reside naturally in seagrass, particularly large juveniles >40 mm carapace length. The greater abundance (and likely survival) of juvenile P. argus that we observed in hard‐bottom habitat as opposed to seagrass, combined with previous studies demonstrating that postlarval P. argus are attracted to, settle in, and metamorphose more quickly in red macroalgae, confirm that macroalgae‐dominated hard‐bottom habitat appears to be the preferred and more optimal nursery for Caribbean spiny lobster.

Mice overexpressing the 5-hydroxytryptamine transporter show no alterations in feeding behaviour and increased non-feeding responses to fenfluramine - A. Pringle; K. A. Jennings; S. Line; D. M. Bannerman; S. Higgs; T. Sharp (Psychopharmacology, 2008)

The potential for seaweed resource development in subarctic Canada; Nunavik, Ungava Bay - G. Sharp; M. Allard; A. Lewis; R. Semple; G. Rochefort (Journal of Applied Phycology, 2008)

Simultaneous blockade of 5-HT1A/B receptors and 5-HT transporters results in acute increases in extracellular 5-HT in both rats and guinea pigs: in vivo characterization of the novel 5-HT1A/B receptor antagonist/5-HT transport inhibitor SB-649915-B - Zoë A. Hughes; Kathryn R. Starr; Claire M. Scott; Michael J. Newson; Trevor Sharp; Jeannette M. Watson; Jim J. Hagan; Lee A. Dawson (Psychopharmacology, 2007)

Interaction of the novel antipsychotic aripiprazole with 5-HT1A and 5-HT2A receptors: functional receptor-binding and in vivo electrophysiological studies - Arlene D. Stark; Shaun Jordan; Kelly A. Allers; Robert L. Bertekap; Ruoyan Chen; Tanaz Mistry Kannan; Thaddeus F. Molski; Frank D. Yocca; Trevor Sharp; Tetsuro Kikuchi; Kevin D. Burris (Psychopharmacology, 2007)

Changes in the Brown Seaweed Ascophyllum Nodosum (L.) Le Jol. Plant Morphology and Biomass Produced by Cutter Rake Harvests in Southern New Brunswick, Canada - Raul A. Ugarte; Glyn Sharp; Bruce Moore (Journal of Applied Phycology, 2006)

Development and genetic mapping of sequence-tagged microsatellites (STMs) in bread wheat (Triticum aestivum L.) - M. J. Hayden; P. Stephenson; A. M. Logojan; D. Khatkar; C. Rogers; J. Elsden; R. M. D. Koebner; J. W. Snape; P. J. Sharp (Theoretical and Applied Genetics, 2006)

Differential involvement of serotonin and dopamine systems in cost-benefit decisions about delay or effort - F. Denk; M. E. Walton; K. A. Jennings; T. Sharp; M. F. S. Rushworth; D. M. Bannerman (Psychopharmacology, 2005)

Nuclear BAG-1 expression inhibits apoptosis in colorectal adenoma-derived epithelial cells - J. D. Barnes; N. J. Arhel; S. S. Lee; A. Sharp; M. Al-Okail; G. Packham; A. Hague; C. Paraskeva; A. C. Williams (Apoptosis, 2005)

A new approach to extending the wheat marker pool by anchored PCR amplification of compound SSRs - M. J. Hayden; P. Stephenson; A. M. Logojan; D. Khatkar; C. Rogers; R. M. D. Koebner; J. W. Snape; P. J. Sharp (Theoretical and Applied Genetics, 2004)

Transfection of MDA-MB-231 human breast carcinoma cells with bone sialoprotein (BSP) stimulates migration and invasion in vitro and growth of primary and secondary tumors in nude mice - Julie A. Sharp; Mark Waltham; Elizabeth D. Williams; Michael A. Henderson; Erik W. Thompson (Clinical & Experimental Metastasis, 2004)

Construction and characterisation of a hexaploid wheat (Triticum aestivum L.) BAC library from the reference germplasm ‘Chinese Spring’ - S. Allouis; G. Moore; A. Bellec; R. Sharp; P. Faivre Rampant; K. Mortimer; S. Pateyron; T. N. Foote; S. Griffiths; M. Caboche; B. Chalhoub (Cereal Research Communications, 2003)

Correlation between extent of osteolytic damage and metastatic burden of human breast cancer metastasis in nude mice: Real-time PCR quantitation - Angus M. Tester; Julie A. Sharp; Nirada Dhanesuan; Mark Waltham; Erik W. Thompson (Clinical & Experimental Metastasis, 2002)

Genetic mapping of 66 new microsatellite (SSR) loci in bread wheat - P. Gupta; H. Balyan; K. Edwards; P. Isaac; V. Korzun; M. Röder; M.–F. Gautier; P. Joudrier; A. Schlatter; J. Dubcovsky; R. De la Pena; M. Khairallah; et al. (Theoretical and Applied Genetics, 2002)

Characterisation of Triticum vavilovii-derived stripe rust resistance using genetic, cytogenetic and molecular analyses and its marker-assisted selection - H. S. Bariana; G. N. Brown; N. U. Ahmed; S. Khatkar; R. L. Conner; C. R. Wellings; S. Haley; P. J. Sharp; A. Laroche (Theoretical and Applied Genetics, 2002)

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Comparison of microbial populations in model and natural rumens using 16S ribosomal RNA‐targeted probes - Cherie J. Ziemer; Richard Sharp; Marshall D. Stern; Michael A. Cotta; Terence R. Whitehead; David A. Stahl (Environmental Microbiology, 2000)
A model rumen system, dual‐flow continuous culture fermenters, was evaluated by two comparative criteria in two experiments using ribosomal (r)RNA‐targeted DNA probes to compare key microbial groups in samples. The initial experiment measured temporal changes in population structure during adaptation of ruminal microbial populations in fermenters over 240 h. The fermenter inoculum contained 34.9% Bacteria, 60.1% Eukarya and 6.8% Archaea measured as a fraction of total small subunit (SSU) rRNA quantified using a universal probe. The cellulolytic bacterial genus Fibrobacter comprised 9.5% of total SSU rRNA in the inoculum. After 240 h of fermenter operation, the average abundance was 80.9% Bacteria, 6.1% Eukarya, 5.1% Archaea and Fibrobacter genus accounted for 6.6% of the total SSU rRNA. Divergence between ruminal and fermenter population structure was evaluated in the second experiment and samples were classified as ruminal, inoculum or fermenter (96, 120, 144 and 168 h of fermenter operation). Fermenter samples had higher relative abundances of Bacteria (84.5%) and Archaea (2.1%) and lower relative abundances of Eukarya (1.8%) than ruminal samples (average 48.0% Bacteria, 1.3% Archaea and 61.5% Eukarya). The relative abundance of Fibrobacter was similar in all samples, averaging 2.5%. The ruminal and fermenter samples had similar proportions of F. succinogenes and F. succinogenes subgroup 3 (as a percentage of Fibrobacter SSU rRNA). Fibrobacter succinogenes subgroup 1 and F. intestinalis proportions of Fibrobacter were lower in fermenter samples (8.2% and 0.7% respectively) than in ruminal samples (28.4% and 2.2% respectively). Fermenters were able to maintain a core prokaryotic community structure similar to the native microbial community in the rumen. Although protozoa populations were lost, maintenance of Fibrobacter and archaeal populations indicated that the model system supported a functional community structure similar to the rumen. This model rumen system may serve as a suitable tool for studying aspects of ruminal microbial ecology and may resolve some of the relationships between microbial community structure and function by providing control of experimental conditions.

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)

Duplication of 7p12.1-p13, including GRB10 and IGFBP1 , in a mother and daughter with features of Silver-Russell syndrome - C.A. Joyce; A. Sharp; J.M. Walker; H. Bullman; I.K. Temple (Human Genetics, 1999)

Duplication of 7p12.1-p13, including GRB10 and IGFBP1, in a mother and daughter with features of Silver-Russell syndrome - C.A. Joyce; A. Sharp; J.M. Walker; H. Bullman; I.K. Temple (Human Genetics, 1999)

Accurate scale up of two phase flow using renormalization and nonuniform coarsening - Timothy C. Wallstrom; Shuling Hou; Michael A. Christie; Louis J. Durlofsky; David H. Sharp (Computational Geosciences, 1999)

Chromosome aberrations in wheat nullisomic-tetrasomic and ditelosomic lines - K. M. Devos; M. E. Sorrells; J. A. Anderson; T. E. Miller; S. M. Reader; A. J. Lukaszewski; J. Dubcovsky; P. J. Sharp; J. Faris; M. D. Gale (Cereal Research Communications, 1999)

Genotypic and phenotypic characterization of six new recombinant congenic strains derived from NOD/Shi and CBA/J genomes - Peter C. Reifsnyder; Jeffry C. Flynn; Amanda L. Gavin; Eric A. Simone; John J. Sharp; Lieselotte Herberg; Edward H. Leiter (Mammalian Genome, 1999)

A study of females with deletions of the short arm of the X chromosome - Rowena S. James; Brian Coppin; Paola Dalton; Nicholas R. Dennis; Caroline Mitchell; Andrew J. Sharp; David H. Skuse; N. Simon Thomas; P. A. Jacobs (Human Genetics, 1998)

The effect of infusion of hypertonic saline on glomerular filtration rate and arginine vasotocin, prolactin and aldosterone in the domestic chicken - A. M. Leary; J. R. Roberts; P. J. Sharp (Journal of Comparative Physiology B, 1998)

Electron-beam induced amorphization of stishovite: Silicon-coordination change observed using Si K -edge extended electron energy-loss fine structure - P. A. van Aken; T. G. Sharp; F. Seifert (Physics and Chemistry of Minerals, 1998)

Gender comparison of peak oxygen uptake: repetitive box lifting versus treadmill running - Bradley C. Nindl; Marilyn A. Sharp; Robert P. Mello; Valerie J. Rice; Michelle M. Murphy; John F. Patton (European Journal of Applied Physiology, 1997)

Increase of 5-HT 7 (serotonin-7) and 5-HT 1A (serotonin-1A) receptor mRNA expression in rat hippocampus after adrenalectomy - S. Le Corre; T. Sharp; A. H. Young; P. J. Harrison (Psychopharmacology, 1997)